Emulsified asphalt, emulsified asphalt cold-recycled mixture and preparation method of emulsified asphalt cold-recycled mixture

By using a composite system of cashew nut shell liquid and vanillin-modified polyurethane prepolymer, the problems of low performance of base asphalt and difficulty in emulsification of modified asphalt in cold recycled mixtures were solved, improving the strength and water damage resistance of the mixture and extending the service life of the pavement.

CN121006080APending Publication Date: 2025-11-25ZHENJIANG SOBUTE NEW MATERIAL CO LTD +2

Patent Information

Application Number
CN202510941638.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

The existing cold recycled asphalt mixtures have low base asphalt performance, difficult modified asphalt emulsification, and limited performance improvement, resulting in problems such as low strength and easy cracking at low temperatures.

Method used

High-performance emulsified asphalt was prepared by using cashew nut shell liquid and vanillin-modified polyurethane prepolymer as modifiers, combined with cationic emulsifiers and stabilizers, forming a rigid-flexible-crosslinked network composite system, which enhances the cohesive strength and water damage resistance of the asphalt.

Benefits of technology

It significantly improves the early wear resistance, road performance and fatigue resistance of cold recycled mixtures, extends the service life of pavement, increases splitting strength by 30%-50% at 15℃ and by 50%-70% at low temperatures, and has excellent resistance to water damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121006080A_ABST
    Figure CN121006080A_ABST
Patent Text Reader

Abstract

The invention provides emulsified asphalt, an emulsified asphalt cold recycled mixture and a preparation method thereof, and the emulsified asphalt comprises the following components in percentage by mass: 40%-55% of matrix asphalt, 5%-20% of a modifier, 10%-15% of an emulsifier and 25%-30% of water, the modifier is selected from any one of atactic polypropylene, terpene resin, epoxy resin, rubber resin and modified polyurethane prepolymer; the modified polyurethane prepolymer is obtained by modifying a polyurethane prepolymer through cashew nut shell liquid and vanillin. The cashew nut shell liquid and the vanillin are used for modifying the prepolymer, and a composite system with rigidity (benzene ring), flexibility (aliphatic chain) and a cross-linked network (polyurethane) is formed; the mechanical property, water damage resistance and the like of the prepared high-performance emulsified asphalt are greatly improved, the early-stage wear resistance, pavement performance and fatigue resistance of a cold recycled mixture can be remarkably improved, and the service life of a pavement is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of emulsified asphalt technology, specifically to an emulsified asphalt, an emulsified asphalt cold recycled mixture, and a method for preparing the same. Background Technology

[0002] Asphalt pavement is widely used in China due to its numerous advantages. However, with long-term loads and ultraviolet radiation, asphalt pavements gradually develop defects and age, requiring resurfacing and resulting in a large amount of old asphalt mixture. This old mixture can be reused on pavements using recycling technology, with emulsified asphalt recycling being a popular approach due to its high proportion of old asphalt and environmentally friendly construction methods. However, the current conventional formula for cold recycling of emulsified asphalt uses emulsified asphalt produced with slow-setting and slow-curing emulsifiers, combined with cement and old asphalt mixtures, and then compacted to form a cold recycled mixture. However, this process is slow to form, with slow penetration of the old asphalt, slow strength improvement in the later stages, and the overall strength being significantly affected by the old asphalt mixture.

[0003] Cold-recycled asphalt mixtures can be used as flexible base and subbase layers for asphalt pavements, and can be used to repair defects in surface and base layers. It is a normal-temperature construction method with minimal environmental impact, and cold recycling can save 40%–50% of the total investment, achieving energy conservation and emission reduction. However, the strength formation characteristics of cold-recycled mixtures result in weaker performance. Currently, cold recycling faces the following problems: ① Low performance of the base asphalt; the performance of the emulsion evaporation residue of the base asphalt decreases, and its adhesion and water resistance are lower than those of hot-mixed asphalt; ② Difficulty in emulsifying modified asphalt, especially SBS modified asphalt, as most emulsifiers are fast-cracking and cannot be used in cold recycling; ③ Limited performance improvement. Currently, the commonly used method is pre-emulsification followed by modification, with waterborne epoxy + 10%, SBR emulsion 0-5%, and SBS emulsion + 20% or more. This method offers limited performance improvement and has low cost-effectiveness.

[0004] Patent CN 107936594 A discloses an emulsified asphalt for cold recycling and its preparation method. The method involves mixing base asphalt, hydrogenated SBS, and chloroprene rubber under heating and stirring to react. Mineral powder is then added and the mixture is stirred until homogeneous to obtain modified asphalt. An emulsifier is added to water and dissolved by stirring. The prepared modified asphalt is then added to the mixture, and emulsification is performed using a colloid mill to obtain the emulsified asphalt. The emulsified asphalt for cold recycling provided by this invention is simple to prepare and easy to store. It can be prefabricated at the factory and used in on-site asphalt recycling. It exhibits good performance and high stability under low-temperature conditions. Furthermore, the preparation method provided by this invention is simple, uses widely available materials, and is environmentally friendly.

[0005] Patent CN 115850984 A provides a silane coupling agent modified emulsified asphalt, which is prepared by the following components by mass percentage: 40-50% base asphalt, 3-10% modifier, 0.5-2% emulsifier, 0.5-3% silane coupling agent, and 35-50% water. The preparation method includes the following steps: (1) preheating the base asphalt and setting it aside; mixing the emulsifier and water to prepare an emulsifier aqueous solution, preheating it, and setting it aside; (2) slowly and evenly adding the preheated base asphalt from step (1) to the preheated emulsifier aqueous solution, and emulsifying it by high-speed stirring to form emulsified asphalt; (3) adding the modifier and silane coupling agent to the emulsified asphalt from step (2), continuing to emulsify by high-speed stirring, and then taking it out and cooling it to obtain the silane coupling agent modified emulsified asphalt.

[0006] Patent CN 118978811 A discloses a silica emulsified asphalt and a recycled asphalt mixture, comprising, by weight percentage: 5-10% water-soluble silicate, 80-90% glass microsphere-modified cold recycled emulsified asphalt, and 5-10% recycling agent emulsion; the water-soluble silicate is an acidic silicate solution or a neutral silicate solution; the glass microsphere-modified cold recycled emulsified asphalt comprises the following raw materials in parts by weight: 50-65 parts base asphalt, 1-4 parts glass microspheres, 2.0-4.0 parts emulsifier, 35-45 parts water, and 0.2-1 parts inorganic acid; the glass microspheres are oleophilic glass microspheres with a particle size ≥170 mesh and a silica content ≥67%, which improves the molding speed of the cold recycled mixture and ensures the strength after rapid molding, so that even if core is taken after 1 day, the crack strength and freeze-thaw strength ratio meet the requirements.

[0007] In summary, providing a high-performance emulsified asphalt to address the current issues of low strength and easy cracking at low temperatures in cold recycled asphalt is an urgent problem to be solved. Summary of the Invention

[0008] To address the shortcomings of existing cold recycled asphalt mixtures, such as low performance of base asphalt, difficulty in emulsifying modified asphalt, and limited performance improvement, this application provides emulsified asphalt, emulsified asphalt cold recycled mixture, and its preparation method. The prepared high-performance emulsified asphalt exhibits significantly improved mechanical properties and water damage resistance, and can significantly improve the early abrasion resistance, road performance, and fatigue resistance of cold recycled mixtures, effectively extending the service life of pavements.

[0009] The specific technical solution of this application is as follows:

[0010] An emulsified bitumen comprising, by weight percentage:

[0011] The base asphalt is 40%–55%, the modifier is 5%–20%, the emulsifier is 10%–15%, and the water is 25%–30%.

[0012] The above-mentioned modifier is selected from any one of atactic polypropylene, terpene resin, epoxy resin, rubber resin, and modified polyurethane prepolymer;

[0013] The above-mentioned modified polyurethane prepolymer was obtained by modifying the polyurethane prepolymer with cashew nut shell liquid and vanillin.

[0014] The modified polyurethane prepolymer was prepared by the following steps: (a) a polyether polyol was polymerized with diisocyanate to generate a terminal-NCO prepolymer; (b) cashew nut shell liquid and vanillin were added to the prepolymer for an addition reaction; (c) a trace amount of ethanol was added to terminate the reaction, and the solvent and bubbles were removed under vacuum to obtain the modified prepolymer.

[0015] In step (a), the amounts of polyether polyol and diisocyanate satisfy NCO:OH = (3-4):1; the polymerization reaction temperature in step (a) is 80±2℃, and the reaction time is 2-3h. Preferably, the molecular weight of the polyether polyol is 1000-1500g / mol (functionality f = 2-3).

[0016] In step (b), the mass ratio of cashew nut shell liquid, vanillin, and prepolymer is 2:1:(5-6), preferably 2:1:5.3, which satisfies NCO:OH = 1.2:1. The addition reaction temperature in step (b) is 60±2℃, and the reaction time is 3-4 hours. The reaction time and temperature are strictly controlled to avoid over-reaction or incomplete reaction. The addition reaction is carried out under inert gas protection, and dibutyltin dilaurate (DBTDL) is used as a catalyst to promote the reaction. The amount of catalyst used is 0.1%–0.3%, preferably 0.2%.

[0017] Cashew nut shell liquid can be obtained through the following process: First, dry cashew nut shells are crushed to 40-60 mesh; then, using a Soxhlet extractor with ethanol as the solvent, the mixture is refluxed for 6-8 hours; finally, the solvent is removed by rotary evaporation to obtain a dark brown viscous liquid. While cashew phenol is more suitable for the preparation of the modified polyurethane prepolymer of this application, directly using cashew nut shell liquid avoids subsequent decarboxylation treatment, simplifying the process. Furthermore, the combined use of this application and vanillin results in a modified polyurethane prepolymer that, when applied to asphalt, achieves better performance improvements.

[0018] Step (c) is used to determine when the reaction is terminated by monitoring at 2270 cm⁻¹. -1The disappearance of the -NCO characteristic peak is sufficient; the specific operation for vacuum desolventizing and bubble removal is as follows: after vacuum desolventizing at 60℃ and -0.09 to -0.08MPa for 1-1.5h, degas at -0.098 to -0.06MPa for 30-35min; preferably, vacuum desolventizing at 60℃ and -0.085MPa for 1 hour, and then increasing to -0.098MPa for 30min.

[0019] The emulsifier mentioned above is a cationic emulsifier.

[0020] The aforementioned cationic emulsifier is selected from at least one of quaternary ammonium salts, alkylamines, amides, imidazoline compounds, ethylene oxide diamines, and aminated lignins.

[0021] The emulsified asphalt also includes a stabilizer, which is selected from any one of lecithin, cellulose ether, and bentonite; the amount of the stabilizer used is 0.3% to 0.5%.

[0022] The preparation method of emulsified asphalt includes the following steps: (1) preparing soap solution: mixing emulsifier and water at high speed to prepare soap solution, keeping it warm and ready for use; (2) preparing modified asphalt: adding modifier to preheated base asphalt to modify it, and obtaining modified asphalt; (3) preparing emulsified asphalt: adding the modified asphalt from step (2) to the soap solution from step (1) to emulsify it, and obtaining emulsified asphalt.

[0023] The shearing rate of step (1) is 1800-2000 r / min, the temperature is 70-80℃, and the holding temperature is 80±2℃; the preheating temperature of step (2) is 140±2℃, the modification conditions are a stirring rate of 1800-2000 r / min and a stirring time of 45-60 min; the emulsification conditions of step (3) are a shearing rate of 500-600 r / min and a shearing time of 5-8 min.

[0024] In step (1) above, hydrochloric acid is added to adjust the pH of the soap solution to 1.5-2.0 during the preparation process; the pH adjuster mentioned above is any one of hydrochloric acid, sulfuric acid, phosphoric acid, or oxalic acid.

[0025] Emulsified asphalt cold recycled mixture comprises the following raw materials in parts by weight: 100 parts asphalt pavement recycled material, 3-5 parts emulsified asphalt, 1.5-3 parts cement, and 3-5 parts water. To use, simply mix all the raw materials of the emulsified asphalt recycled mixture.

[0026] The aforementioned recycled asphalt pavement materials include 30-40 parts of recycled asphalt pavement material with a particle size of 0-5mm, 25-30 parts of recycled asphalt pavement material with a particle size of 5-10mm, 20-25 parts of recycled asphalt pavement material with a particle size of 10-20mm, 10-12 parts of virgin material with a particle size of 10-20mm, and 2-3 parts of mineral powder.

[0027] The above-mentioned mineral powder is limestone mineral powder.

[0028] This application has the following advantages over the prior art:

[0029] (1) This application uses cashew nut shell liquid and vanillin modified prepolymer to form a composite system with rigid (benzene ring) + flexible (aliphatic chain) + cross-linked network (polyurethane); in this composite system, the urethane bonds of the reaction product form hydrogen bonds or covalent bonds with the polar components (such as asphaltenes) in the asphalt, reducing internal defects and enhancing cohesive strength; the benzene ring structure of vanillin and the hard segments of polyurethane form rigid micro-regions to resist deformation under external force; the cashew phenol long chain of cashew nut shell liquid is compatible with asphalt to form a flexible-rigid interpenetrating structure to avoid brittle fracture; the phenolic hydroxyl groups of vanillin and the aromatic structure of cashew nut shell liquid synergistically capture free radicals and absorb ultraviolet rays (delay aging); the aliphatic chain plasticization of cashew nut shell liquid + the flexible segments of vanillin increase the low temperature ductility (≥25%) and reduce the creep stiffness of BBR (20%~30%).

[0030] (2) The modified asphalt of this application has a splitting strength of 1.5 to 1.8 MPa at 15°C, which is 30% to 50% higher than that of unmodified asphalt (0.8 to 1.2 MPa); the improvement is even more significant at low temperature (-10°C), reaching 50% to 70%, because the cross-linking network inhibits low-temperature brittleness.

[0031] (3) The -NH-COO- bonds in the modified polyurethane prepolymer form hydrogen bonds or covalent bonds with the hydroxyl groups (-OH) on the surface of aggregates (such as limestone), reducing the intrusion of water molecules into the interface; the long fatty chains of cashew nut shell liquid form a hydrophobic layer at the asphalt-aggregate interface, blocking water penetration; the benzene ring structure of vanillin fills the micropores of asphalt, reducing capillary water absorption; the polyurethane crosslinking network enhances the elastic recovery ability of the asphalt film and resists the peeling caused by hydrodynamic scouring; the asphalt obtained in this application has the following water damage resistance: TSR (freeze-thaw splitting strength ratio) ≥ 85%, and peeling rate ≤ 5%. Attached Figure Description

[0032] Figure 1 The strength development curves of Marshall specimens formed from the high-performance emulsified asphalt cold recycled mixture and the ordinary emulsified asphalt cold recycled mixture directly emulsified from the base asphalt in Example 1 are shown. Detailed Implementation

[0033] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0034] Unless otherwise specified, all chemical reagents and materials in this invention are purchased from the market or synthesized from raw materials purchased from the market.

[0035] The asphalt used was 70# base asphalt produced in Hai'an; the atactic polypropylene had an average molecular weight of 2300, a relative density of 0.9, and a softening point of 110℃; the terpene resin had an average molecular weight of 2200, a relative density of 0.98, and a softening point of 110℃; the emulsifier selected was Runqiang produced by Jiangsu Subote New Material Co., Ltd. Cationic emulsifier; epoxy resin E41 produced by Dongguan Aifeng New Material Technology Co., Ltd.; bentonite produced by Xinrun Building Materials Factory of Pingqiao District, Xinyang City; lecithin produced by Xi'an Tongze Biotechnology Co., Ltd.

[0036] Modified polyurethane prepolymer A was prepared by the following steps: (a) Polyether polyol was polymerized with diisocyanate to generate terminal-NCO prepolymer; (b) Cashew nut shell liquid and vanillin were added to the prepolymer for addition reaction; (c) A trace amount of ethanol was added to terminate the reaction, and the solvent and bubbles were removed under vacuum to obtain the modified prepolymer.

[0037] The polyether polyol has a molecular weight of 1000 g / mol, a functionality f = 2, and is used in an amount of 1 mol. The amounts of polyether polyol and diisocyanate satisfy NCO:OH = 4:1. The polymerization reaction temperature in step (a) is 80℃, and the reaction time is 2 h. In step (b), the mass ratio of cashew nut shell liquid, vanillin, and prepolymer is 2:1:5.3. The addition reaction temperature in step (b) is 60℃, and the reaction time is 3 h. The addition reaction is carried out under inert gas protection, and the catalyst dibutyltin dilaurate (DBTDL) is used to promote the reaction, with a catalyst dosage of 0.2%. The termination of the reaction in step (c) is determined by monitoring 2270 cm⁻¹. -1 The disappearance of the -NCO characteristic peak is sufficient; the specific operation for vacuum desolventizing and bubble removal is as follows: desolventize under vacuum at 60℃ and -0.085MPa for 1 hour, and then increase to -0.098MPa for degassing for 30 minutes.

[0038] The preparation process of modified polyurethane prepolymer B is the same as that of modified polyurethane prepolymer A, except that in step (b), the mass ratio of cashew shell liquid, vanillin, and prepolymer is 2:1:6.

[0039] The preparation process of modified polyurethane prepolymer C is the same as that of modified polyurethane prepolymer A, except that in step (b), the mass ratio of cashew shell liquid, vanillin and prepolymer is 2:1:7.

[0040] The preparation process of modified polyurethane prepolymer D is the same as that of modified polyurethane prepolymer A, except that in step (b), the mass ratio of cashew shell liquid to prepolymer is 3:4.

[0041] The preparation process of modified polyurethane prepolymer E is the same as that of modified polyurethane prepolymer A, except that in step (b), the mass ratio of vanillin to prepolymer is 3:7.8.

[0042] The formulation of emulsified asphalt R in the various embodiments and comparative examples of this invention is shown in Table 1 below:

[0043] Table 1. Mixing ratio of high-performance emulsified asphalt

[0044] Base asphalt Modifier emulsifier water stabilizer R1 55% 7% atactic polypropylene 10% hexadecyltrimethylammonium bromide 27.7% 0.3% lecithin R2 45% 10% epoxy resin E41 12% Alkylpropylene Diamine 32.5% 0.5% bentonite R3 53% 7% Modified Polyurethane Prepolymer A 10% Aminated Lignin Emulsifier 29.6% 0.4% lecithin R4 50% 10% terpene resin 14% imidazoline emulsifier 25.7% 0.3% bentonite R5 40% 20% Modified Polyurethane Prepolymer B 15% Alkylpropylene Diamine 25% 0 R6 53% 7% Modified Polyurethane Prepolymer C 10% Aminated Lignin Emulsifier 29.6% 0.4% lecithin R7 53% 7% Modified Polyurethane Prepolymer D 10% Aminated Lignin Emulsifier 29.6% 0.4% lecithin R8 53% 7% Modified Polyurethane Prepolymer E 10% Aminated Lignin Emulsifier 29.6% 0.4% lecithin

[0045] The specific preparation process of emulsified asphalt in each embodiment and comparative example is as follows:

[0046] The first step is to prepare soap solution by mixing emulsifier, stabilizer and water using a high-speed shearing apparatus at a shearing speed of 1900 r / min and controlling the soap solution temperature at 80℃. Then, an appropriate amount of hydrochloric acid is added to adjust the pH value of the soap solution to 1.8. The soap solution is then placed in an 80℃ water bath for heat preservation until use.

[0047] The second step is to put the asphalt into an oil bath and heat it to a constant temperature of 140°C. The stirring speed is 2000 r / min. While stirring, the modifier is added. The stirring time is 60 min. The modified asphalt is then placed in an oven for later use.

[0048] The third step is to first pour the soap solution into the colloid mill, then slowly add the preheated modified asphalt into the soap solution, with a shearing speed of 400 r / min and a shearing time of 6 min, and then cool it for later use.

[0049] The milling material (RAP) used was a sample from the Zibo section of the Jinan-Qingdao Expressway reconstruction and expansion project, with a moisture content of 0.1%.

[0050] The gradation of recycled asphalt pavement materials is shown in Table 2, in %:

[0051] Table 2 Mineral Gradation / %

[0052] <![CDATA[RAP 0-5 ]]> <![CDATA[RAP 5-10 ]]> <![CDATA[RAP 10-20 ]]> <![CDATA[New material 10-20 > Mineral powder 39.5 27 21 10 2.5

[0053] The raw material proportions in the emulsified asphalt cold recycled mixture are shown in Table 3 below. The numbers corresponding to emulsified asphalt R correspond to the numbers of the examples and comparative examples:

[0054] Table 3. Mix proportions of high-performance emulsified asphalt cold recycled mixture / %

[0055] Minerals Emulsified asphalt R cement water 100 3.99 1.5 4.08

[0056] Specimens were molded according to the mix proportions, and the porosity, dry splitting strength at 15℃, dry-wet splitting strength ratio, and freeze-thaw splitting strength ratio of the mixture were examined, referring to standard JTG / T 5521-2019 Technical Specification for Recycling Asphalt Pavement of Highways (page 23, Tables 6.3.5-6.3.6); the stripping rate referenced standard JTG E20-2011 T 0666-2011; rutting test JTG E20-2011 T 0719; static creep test JTG E20 T 0726; and low-temperature bending test JTG E20-2011 T 0725. The control group was a cold recycled mixture of ordinary emulsified asphalt directly emulsified from base asphalt. The results are shown in Table 4:

[0057] Table 4 Comprehensive Performance of Mixture

[0058]

[0059] According to the data in Table 4, the molded specimens obtained using the raw materials and proportions of the emulsified asphalt of this application showed better performance than the control group. Comparative Example 1 used excessive amounts of prepolymer, resulting in excessively high -NCO content, and the freeze-thaw splitting strength ratio and other properties of the specimens were significantly lower than those of Example 3. Comparative Example 2 only used cashew nut shell liquid for polyurethane modification, lacking the synergistic effect of vanillin, leading to easy creep at high temperatures and decreased tear resistance. Comparative Example 3 only used vanillin for polyurethane modification, resulting in increased material hardness, decreased failure strain energy, and susceptibility to low-temperature cracking.

[0060] Marshall specimens molded in Example 3 and the control group were cured in molds at 20°C and 60% humidity for 1 to 7 days, and their splitting strength was tested. The results are as follows: Figure 1 As shown in the figure, the 1-day splitting tensile strength of mixtures prepared from different emulsified asphalts is the same. However, starting from the 2-day strength, the splitting tensile strength of mixtures prepared from high-performance emulsified asphalt is significantly higher than that of cold-recycled mixtures prepared from ordinary emulsified asphalt. The splitting tensile strength of high-performance emulsified asphalt cold-recycled mixtures increases almost linearly with the extension of curing age.

[0061] The technical solution of this application has been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this invention. The descriptions of the embodiments above are only for the purpose of helping to understand the method and core ideas of this invention, including the best mode, and also to enable any person skilled in the art to practice this invention. It should be noted that for those skilled in the art, several improvements and modifications can be made to this invention without departing from the principles of this invention, and these improvements and modifications also fall within the protection scope of the claims of this invention. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims. For those skilled in the art, it is understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of this invention, and the scope of this invention is defined by the appended claims and their equivalents.

Claims

1. An emulsified asphalt, characterized in that, Included as a percentage by weight: The matrix asphalt comprises 40%–55%, modifier 5%–20%, emulsifier 10%–15%, and water 25%–30%; the modifier is selected from any one of atactic polypropylene, terpene resin, epoxy resin, rubber resin, and modified polyurethane prepolymer. The modified polyurethane prepolymer was obtained by modifying the polyurethane prepolymer with cashew nut shell liquid and vanillin.

2. The emulsified asphalt according to claim 1, characterized in that, The modified polyurethane prepolymer was prepared by the following steps: (a) a polyether polyol was polymerized with diisocyanate to generate a terminal-NCO prepolymer; (b) cashew nut shell liquid and vanillin were added to the prepolymer for an addition reaction; (c) a trace amount of ethanol was added to terminate the reaction, and the solvent and bubbles were removed under vacuum to obtain the modified prepolymer.

3. The emulsified asphalt according to claim 2, characterized in that: In step (a), the amounts of polyether polyol and diisocyanate used satisfy NCO:OH = (3-4):1; the polymerization reaction temperature in step (a) is 80±2℃, and the reaction time is 2-3h.

4. The emulsified asphalt according to claim 2, characterized in that: In step (b), the mass ratio of cashew shell liquid, vanillin, and prepolymer is 2:1:(5-6); the addition reaction temperature in step (b) is 60±2℃, and the reaction time is 3-4h.

5. The emulsified asphalt according to claim 2, characterized in that: The specific operation of step (c) for vacuum removal of solvent and bubbles is as follows: after vacuum removal of solvent at 60℃ and -0.09 to -0.08 MPa for 1-1.5 h, degas at -0.098 to -0.06 MPa for 30-35 min.

6. The emulsified asphalt according to claim 1, characterized in that: The emulsifier is a cationic emulsifier. Preferably, the cationic emulsifier is selected from at least one of quaternary ammonium salts, alkylamines, amides, imidazoline compounds, ethylene oxide diamines, and aminated lignins.

7. The emulsified asphalt according to claim 1, characterized in that: The emulsified asphalt also includes a stabilizer, which is selected from any one of lecithin, cellulose ether, and bentonite; the amount of the stabilizer is 0.3% to 0.5%.

8. A method for preparing emulsified asphalt according to any one of claims 1-7, characterized in that, The steps include: (1) preparing soap solution: mixing emulsifier and water at high speed to prepare soap solution, keeping it warm and ready for use; (2) Preparation of modified asphalt: Modifier is added to preheated base asphalt to modify it and obtain modified asphalt; (3) Preparation of emulsified asphalt: Modified asphalt from step (2) is added to soap solution from step (1) for emulsification to obtain emulsified asphalt.

9. The preparation method according to claim 8, characterized in that: The shearing rate in step (1) is 1800-2000 r / min, the temperature is 70-80℃, and the holding temperature is 80±2℃; the preheating temperature in step (2) is 140±2℃, and the modification conditions are a stirring rate of 1800-2000 r / min and a stirring time of 45-60 min. The emulsification conditions in step (3) are a shear rate of 500-600 r / min and a shear time of 5-8 min.

10. The preparation method according to claim 8, characterized in that: In step (1), hydrochloric acid is added during the preparation of the soap solution to adjust the pH of the soap solution to 1.5-2.0; the pH adjuster is any one of hydrochloric acid, sulfuric acid, phosphoric acid, or oxalic acid.

11. Emulsified asphalt cold recycled mixture, characterized in that, The raw materials include the following parts by weight: 100 parts of recycled asphalt pavement material, 3-5 parts of emulsified asphalt, 1.5-3 parts of cement, and 3-5 parts of water; wherein the emulsified asphalt is an emulsified asphalt as described in any one of claims 1-7 or an emulsified asphalt prepared by the preparation method described in any one of claims 8-10.

12. The emulsified asphalt recycled mixture according to claim 11, characterized in that: The recycled asphalt pavement material comprises 30-40 parts of recycled asphalt pavement material with a particle size of 0-5mm, 25-30 parts of recycled asphalt pavement material with a particle size of 5-10mm, 20-25 parts of recycled asphalt pavement material with a particle size of 10-20mm, 10-12 parts of virgin material with a particle size of 10-20mm, and 2-3 parts of mineral powder; the mineral powder is limestone mineral powder.

Citation Information

Patent Citations

  • Emulsified asphalt for cold-recycled asphalt and preparation method of emulsified asphalt

    CN107936594A

Cited By

  • High-toughness regenerated asphalt modifier and application thereof in asphalt regeneration

    CN121717975A